University students’ perception of online learning: A case study of Virtual Class learning management system in the University of Lampung - Fajar Riyantika; Khairun Nisa; Budi Kadaryanto (International Journal of Educational Studies in Social Sciences (IJESSS), 2021)
The use of online media to facilitate distant learning during the pandemic has become one of the solutions that can be implemented to support the government's policy of reducing crowds in public spaces. In this case, students at the University of Lampung's Faculty of Teacher Training and Education benefit from an online management system called Virtual Class Unila. This platform is intended for students to use to access resources, download learning modules, and participate in classroom discussions. The Virtual Class was created to assist students with distance learning. However, since the initial implementation of Virtual Class at the start of the pandemic in early 2020, both positive and negative perceptions about its use have emerged. As a result, we were encouraged to ascertain diverse perceptions regarding the use of this sophisticated learning management system among students at the Faculty of Teacher Training and Education, University of Lampung. This study employed a quantitative approach, collecting data via a scaled survey questionnaire. The target participants were 272 students from various departments who were asked to complete a survey regarding their perceptions of the implementation of Virtual Class. The findings of this study are expected to be beneficial for the future maintenance and development of Virtual Class, as well as for determining the optimal method of conducting online learning.